(untitled) (Journal of Economic Research & Business Administration, 2016)
Implementation of the financial activity in modern conditions is im- possible without special methods of analysis and risk management. The function of financial risk management becomes an increasingly important role and becomes one of the most important conditions to ensure financial stability of the enterprise organizations. Financial Risk Management of the company is a specific area of financial management, which is abroad in recent years stood out as a special field of activity - the «risk-management». Financial risk - the risk associated with the probability of loss of fi- nancial resources (cash). Financial risks arose simultaneously with the ap- pearance of money and with the emergence of various types of monetary relations: the investor - the issuer, the lender - the borrower, the seller - the buyer, exporter - importer and others. Financial risks are an integral part of business activity in the market.